PROCESSING EFFECT ON THE MICROBIAL AND PROXIMATE COMPOSITION OF KILISHI AT SOUTH EAST NIGERIA - Okorie, Peter Anyigor (International Journal of Research -GRANTHAALAYAH, 2018)
The proximate and microbiological compositions of kilishi, a processed meat at Abakaliki, southeast of Nigeria was determined in this study. The moisture, protein, fat, and ash contents, including the microbial count of the raw meat and kilishi in the study area were investigated to ascertain the processing effect. The results show that kilishi has higher protein content, fat content and ash content relative to the raw meat with the difference of 17.04 %, 4.66 % and 1.94 %. The moisture content and microbial count of kilishi are lower compared to the raw meat with a difference of 62.00 % and 17.33 cfu/g. The analysis suggests that the kilishi sold at Abakaliki is safe for human consumption.